The impact of CSR on corporate financial performance - DING, David K. (Institutional Knowledge at Singapore Management University, 2017)
We provide one of the first analyses of corporate social responsibility (CSR) and firm performance using only annual financial reports. We document a link between corporate financial performance (CFP) and CSR, although this is not always positive. Specifically, we investigate whether CSR performance can be implied from financial reporting and provide evidence that CSR information implied by financial reports have a significant association with CFP. Furthermore, we provide the first comprehensive study of CSR reporting and link it with CFP in New Zealand.